"Bildungsbürgertum" : Begriffs- und Dogmengeschichte eines Etiketts - Engelhardt, Ulrich 1940- (Industrielle Welt, 1986)
Ulrich Engelhardt: "Bildungsbürgertum". Klett-Cotta Verlag, Stuttgart, 1986. 274 S., geb., 96,- DM